Stokes Flow of Viscous Fluid Past a Micropolar Fluid Spheroid (Advances in Applied Mathematics and Mechanics, 2018)
The Stokes axisymmetric flow of an incompressible viscous fluid past a micropolarfluid spheroid whose shape deviates slightly from that of a sphere is studiedanalytically. The boundary conditions used are the vanishing of the normal velocities,the continuity of the tangential velocities, continuity of shear stresses and spin-vorticityrelation at the surface of the spheroid. The hydrodynamic drag force actingon the fluid spheroid is calculated. An exact solution of the problem is obtained tothe first order in the small parameter characterizing the deformation. It is observedthat due to increase spin parameter value, the drag coefficient decreases. Well knownresults are deduced and comparisons are made with classical viscous fluid and micropolarfluid.